Correlation of malondialdehyde and hearing threshold level at frequency 4000 Hz post gunshot exposure - Nyilo Purnami; Fauzi Helmi; Sri Herawati (Oto Rhino Laryngologica Indonesiana, 2020)
Background: The incidence of acoustic trauma after gunshot exposure in students of the SekolahPolisi Negara (SPN) is quite high. Malondialdehyde (MDA) is a compound that can portray oxidativestress due to free radicals. The correlation between the levels of MDA and the hearing threshold frequencypost gunshot exposure could be used as the base for administering antioxidants to prevent acoustictrauma. Objective: To find out the correlation between the levels of MDA and the hearing thresholdfrequency post gunshot exposure, in East Java SPN students. Method: An observational analytic studywith a retrospective cross sectional approach using secondary data of medical records of the East JavaSPN students batch 2017/2018. The samples were selected by simple random sampling. Result: Out of50 students, the mean of age was 19.62 years. All samples were male with mean 559.17 and standarddeviation (SD) 959.86. The calculation of the 4000 Hz frequency threshold value obtained an averagevalue of 31.52 and SD of 13.4. Hearing loss complaint was found in 1 student (2%). No complaints oftinnitus and vertigo were found. Statistical tests with Pearson correlation between serum MDA levels and4000 Hz frequency threshold values showed a correlation coefficient (r) of 0.74 and p = 0.00 (p<0.05).Conclusion: There was a significant correlation between MDA levels and the hearing threshold at 4000Hz frequency after gunshot exposure in East Java SPN students.Keywords: acoustic trauma, malondialdehyde, hearing threshold level at frequency 4000 HzABSTRAKLatar belakang: Insiden trauma akustik pasca pajanan letusan senjata api pada siswa Sekolah PolisiNegara (SPN) cukup tinggi. Malondialdehid (MDA) merupakan senyawa yang dapat menggambarkanstres oksidatif akibat radikal bebas. Adanya hubungan antara kadar MDA dengan nilai ambang dengarfrekuensi 4000 Hertz (Hz) dapat menjadi dasar pemberian antioksidan untuk pencegahan traumaakustik. Tujuan: Membuktikan hubungan antara kadar MDA dengan nilai ambang dengar frekuensi4000 Hz pasca pajanan letusan senjata api pada siswa SPN Jawa Timur. Metode: Penelitian ini adalahobservasional analitik dengan pendekatan retrospektif cross sectional menggunakan data sekunderberupa rekam medik siswa SPN Jawa Timur angkatan 2017/2018. Sampel dipilih secara simple random sampling. Hasil: Dari 50 siswa, usia rerata adalah 19,62 tahun. Seluruh sampel penelitian adalah laki-laki, rerata=559,17 dan standar deviasi (SD)=959,86. Penghitungan nilai ambang dengar frekuensi 4000 Hz didapatkan hasil nilai rerata=31,52 dan SD=13,4 Keluhan penurunan pendengaran hanya dijumpai pada 1 siswa (2%). Uji statistik dengan korelasi Pearson antara kadar MDA dalam serum dengan nilai ambang dengar frekuensi 4000 Hz didapatkan hasil koefisien korelasi (r) sebesar 0,74 dan p = 0,00 (p<0,05). Kesimpulan: Terdapat hubungan yang signifikan antara kadar MDA dengan nilai ambang dengar frekuensi 4000 Hz pasca pajanan letusan senjata api pada siswa SPN Jawa Timur.Kata kunci: trauma akustik, malondialdehid, nilai ambang dengar frekuensi 4000 Hz